Efficacy of group obstetric consultation in mild to moderate anxiety of pregnancy - Dayhimi, Marjaneh; Kariman, Noorosadat; Baghban, Alireza Akbarzadeh; Shams, Jamal; Hamzehgardeshi, Zeinab; Tayebi, Tahereh; Mortazavi Tabatabaee, Seyyd Abdolreza (Archives of Advances in Biosciences, 2013)
Anxiety is a common mental disorder of pregnancy leading to adverse maternal and fetal pregnancy outcomes. Hence, preparation of effective approaches for reduction of anxiety is an issue of importance. Accordingly, this study was performed to determine the efficacy of group obstetric consultation on anxiety control in pregnant women in non-severe cases. In this randomized clinical trial, 90 pregnant women attending to a Health Care Center in Tehran, Iran from April 2010 to March 2012 with first pregnancy aging from 18 to 35 years and gestational age of eight to eighteen weeks were evaluated. They were randomly assigned into consultation and control groups. The consultation group was designed according to the different needs of pregnancy for five sessions in five weeks (each session 60 to 90 minutes) and the control group only received routine perinatal care. There was statistically significant difference between after-intervention scores in anxiety state (P=0.014); but the anxiety trait showed no difference (P=0.19). Also the changes in trait anxiety scores was more in consultation group compared with control group (P=0.002) that was also seen for anxiety state scores (P=0.0001). Totally, it may be concluded that group consultation is effective in reduction of state and trait anxiety in pregnant women with non-severe non-pathological cases of anxiety.